Generalized classification of modern quantum cryptography and communication methods - Жмурко, Тетяна Олександрівна; Кінзерявий, Василь Миколайович; Юбузова, Халіча Ібрагимівна; Стояновіч, Алєксандар Деспотовіч (Ukrainian Scientific Journal of Information Security, 2015)
Modern powerful computing technology development threatens the confidentiality of information that usually provided by traditional cryptographic means and forces researchers to look for alternative security methods. Given the current trends, these alternatives may be quantum cryptography and communication methods. These methods unlike traditional (classical) analogues use specific unique properties of quantum particles and are based on the inviolability of the quantum physics laws. Existing classifications in quantum cryptography and communications do not include the large number of modern methods. It complicates its study and use in the quantum information security systems development. In the paper modern methods of quantum cryptography and communication were analyzed, their advantages and disadvantages, security assessment to various kinds of cyberattacks were defined, and also the existing classifications of these methods were studied. On the basis of partial generalizations of theoretical positions and practical advances in quantum cryptography, the generalized classification of quantum cryptography and communication methods was constructed. This classification reveals a problem in this area and can extend the possibilities for choosing the appropriate methods for modern quantum information security systems development.